THE EFFECTIVENESS OF PROVISION OF NEW STATIC INFORMATION SIGNAGE: A CASE STUDY OF INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA, GOMBAK CAMPUS - Sahrir, Syazwani; Bachok, Syahriah; Mohamed Osman, Mariana (PLANNING MALAYSIA, 2012)
The provision of road and highway traffic signage on public roads has been regulated in Malaysia, by the Department of Works and Departments of Road Transport Acts, Rules and Regulations 1987. Many studies have focused on the responses and impacts of these types of signage. However, for many private roads which a re not regulated under these Acts, Rules and Regulations, several non-conventional types of signage have been provided. There is lack of study, however, on the impacts of and drivers' responses towards these signages. This study, hence, explores the types, contents and locations of these signage. Additionally, the impacts of and responses towards these signages are evaluated in a controlled campus environment. Using the International Islamic University Malaysia's young student drivers as the unique purposive samples, statistical tests including correlation and chi-square analyses have been conducted. It is preliminary reported that gender and observation frequency, to a certain extent, influenced drivers' responses towards the information conveyed by the signages.